Screening of trace metal supplementation for black water anaerobic digestion - Braga, Adriana F. M.; Pereira, Maria Beatriz O. C. [UNESP]; Zaiat, Marcelo; da Silva, Gustavo H. R. [UNESP]; Fermoso, Fernando G. (Taylor & Francis, 2018)
Community on-site separation of wastewater is a treatment approach that leads to more efficient processes. Black water has high organic matter content and can be a suitable feedstock for anaerobic treatment systems. Biological methane production (BMP) tests were conducted using Plackett–Burman design to screen the effects of adding Fe, Ni, Cu, Co, Mn, Ba and Se, with simulated black water (SBW) as the substrate. In the inoculum, most metals were found mainly in the organic matter/sulfide and residual fractions except for Mn, which was present at 12.3% in the bioavailable fractions (exchangeable and carbonates), and Ba, which was evenly distributed among all the fractions. Ba had a significant negative effect on methane production and Mn addition enhanced the toxic effect. A specific methanogenic activity (SMA) between 18% and 27% lower than the control, was predicted at a total Ba concentration of approximately 1000–1200 mg L−1. Similar SMA was predicted at Ba concentration between 400 and 600 mg L−1 when 0.55 mg L−1 of Mn is added. Se and Cu additions demonstrate the potential to improve the methane production from SBW. The SMA was predicted to reach 12 mLCH4 gCOD−1 d−1 when Cu and Se are supplied at total concentrations of 3.0 mg L−1 and 0.98 mg L−1, respectively.
Keywords: Decentralized sanitation; metal addition; Plackett–Burman design; specific methanogenic activity; synergic effect of metals